Potensi Ekstrak Batang Serai (Cymbopogon citratus) untuk Pengobatan Ikan dari Bakteri Edwarsiella tarda - Misbah Misbah; Javita Putri Aulia; Maharani Maharani; Eka Widhiastuti; Viola Maharani Windy Putri; Sindi Ardila; Tanbiyaskur Tanbiyaskur (Seminar Nasional Lahan Suboptimal, 2021)
Misbah M, Aulia JP, Maharani M, Widhiastuti E, Putri VMW, Ardila S, Tanbiyaskur T. 2021. Potency of lemongrass stem extract (Cymbopogon citratus) for Fish Treatment from Edwarsiella tarda bakteri bacteria. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang  20 Oktober 2021. pp. 782-787. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).  The high demand for fishery products has resulted in cultivators implementing intensive and even super intensive cultivation systems. The intensification of fish farming is characterized by an increase in stocking density followed by an increase in the use of artificial feed which has the potential to become waste and cause disease. To overcome this, alternative actions that are safer and also effective for controlling fish diseases are needed. One alternative is to use herbal plants that are anti-bacterial. By using herbal plants, it will be safer, easier to obtain and also not pose a danger to the surrounding environment. This study aimed to determine the effectiveness of lemongrass stem extract to treat bacterial disease in fish caused by Edwarsiella tarda. Some research results showed that Cymbopogon citratus extract is rich in benefits in herbal medicine. Cymbopogon citratus extract had antibacterial properties that could inhibit the growth of pathogenic bacteria in fish. Phytochemical test results, lemongrass extract contained secondary metabolites such as alkaloids, steroids, terpenoids, phenolics or tannins or flavonoids and saponins. Based on the results of in vitro tests on lemongrass stem extract, it was able to inhibit the growth of Edwarsiella tarda bacteria where the inhibition zone formed after the media was incubated for 24 hours with a size of 21 mm. This proved that lemongrass stem extract can inhibit the growth of Edwarsiella tarda bacteria based on the results of the inhibition test.